Investigation the influence of soil’s moisture regime on their degradation using the remote sensing and ground field verification - Romanciuc, Inna (Scientific Centre for Aerospace Research of the Earth Institute of Geological Science National Academy of Sciences of Ukraine, Kyiv, Ukraine, 2018)
In the article were used the field and distance methods of determination of moisture content in the upper layer of soil cover. Comparison of field measurements of soil moisture and Sentinel-2 image processing results revealed their correlation. On the basis of the moisture content data in the soil layer and the vegetation state analysis the soil fertility prediction was made. The research were done near Berezan, the Baryshivskyi raion in east-central Kiev Oblast of Ukraine.